IN SITU growth redox-active iron-centered particles on graphene sheets for specific capacitance enhancement - Puteri Emme Marina, Mohamad (2017)
Graphene is a unique two-dimensional carbon material having good conductivity, stable chemical properties, and good mechanical properties with large surface area (- 2600 M2 g). Due to the outstanding mechanical and electrical properties, graphene is proposed as an electrode material for supercapacitor applications. Nevertheless, graphene has issues where in the dry state it is tends to agglomerate which hindering its full capability in electrochemical performance. Therefore, an improvement is needed in order to resolve the re-stacking issue. In this study, a facile approach is proposed to enhance the specific capacitance of (N-methylpyrrolidone) NMP-exfoliated graphene. Redox-active nickel hexacyanoferrate (NiFeCN) nanoparticles were grown on the surface of graphene sheets using a co-precipitation method. Apart from the synergetic effect of graphene and NiFeCN in the specific capacitance enhancement, the NiFeCN nanoparticles served as the spacer for graphene sheets to prevent the agglomeration between graphene sheets. This combination performed as a hybrid composite nanomaterial which possessed both electrochemical double layer capacitor (EDLC) and pseudo capacitance. With the above motivation, a graphene-based nanocomposite material has been extensively studied in this thesis. All the materials examined were prepared via simple co-precipitation synthesis techniques with different range of composite ratios (NiFeCN/G-10, NiFeCNIG-25, NiFeCN/G-50, NiFeCNIG-75 and NiFeCNIG-90). Characterization has been done using Fourier transform infrared spectroscopy, X-ray diffraction, energy-dispersive X-ray spectroscopy and field emission scanning electron microscope. Their electrochemical properties were evaluated for supercapacitors using three electrode system configurations. From this experiment, a nanocomposite at a ratio of 25: 75 (NiFeCN/G-25) is shown to have a very high specific capacitance of 113.5 F g-iwhich is 2 times higher than the NMP-exfoliated graphene (52 F g-i) and 6 times higher than the pure NiFeCN (18 F g-i). The findings suggest that the NiFeCN/graphene could be the potential candidate for supercapacitors electrode. The enhanced electrochemical performance of these nanocomposite materials could be attributed to the dual contributions of graphene and nanoparticles. The results of this study indicated the graphene nanocomposite has great potential for application to practical energy storage devices.